2010
DOI: 10.3109/13693781003677494
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformansandCryptococcus gattiigenes preferentially expressed during rat macrophage infection

Abstract: Cryptococcus neoformans and Cryptococcus gattii are encapsulated yeast agents of cryptococcosis and facultative intracellular pathogens. The interaction of these yeasts with macrophages is essential for containing the infection. However, Cryptococcus spp. overcome this initial host defense barrier using a unique pathogenic strategy involving intracellular replication and cytoplasmic accumulation of polysaccharide-containing vesicles. Here, we employed representational difference analysis (RDA) to identify C. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Overall, the internalized fungal cells appear to experience a nutrient-limited and stressful environment. Similar but more limited results were obtained in a study to characterize and compare the expression of C. neoformans and C. gattii genes during intracellular growth in rat peritoneal macrophages by representational difference analysis (RDA) (45).…”
supporting
confidence: 54%
“…Overall, the internalized fungal cells appear to experience a nutrient-limited and stressful environment. Similar but more limited results were obtained in a study to characterize and compare the expression of C. neoformans and C. gattii genes during intracellular growth in rat peritoneal macrophages by representational difference analysis (RDA) (45).…”
supporting
confidence: 54%
“…Variations in myo-inositol transporters in the VGI isolates are also noteworthy because myo-inositol transport has been implicated in mating and virulence (70). Additionally, transcriptome studies revealed that the transcript for myo-inositol phosphate synthase ( MYO1 ) is abundant in vivo and that an inositol/phosphatidyl inositol phosphatase is upregulated upon phagocytosis of C. gattii by rat peritoneal macrophages (7173). Recently, it was demonstrated that phosphatidylinositol 4-kinase is required for survival ex vivo in the hostile cerebrospinal fluid environment and within macrophages and for full virulence (74).…”
Section: Resultsmentioning
confidence: 99%
“…CnAfr1 seems to interfere with the pathway of phagolysosome maturation, as the early endosome marker Rab5 and late marker Rab7 are less detected upon the overexpression of the CnAFR1 gene [ 149 ]. Moreover, Goulart and colleagues have reported the upregulation of other ABC transporters in C. neoformans cells phagocyted by peritoneal macrophages [ 150 ], highlighting the importance these transporters within the study of the Cryptococcus species survival in the host.…”
Section: Mdr Transporters In Fungal Pathogens: Playing a Role In Vmentioning
confidence: 99%